2020
DOI: 10.31235/osf.io/3g2u6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attendance Boundary Policies and the Limits to Combating School Segregation

Abstract: What is the efficacy of redrawing school attendance boundaries as a desegregation policy? To provide causal evidence on this question we employ novel data with unprecedented detail on the universe of Danish children and exploit changes in attendance boundaries over time. Households defy reassignments to schools with lower socioeconomic status. There is a strong social gradient in defiance, as resourceful households are more sensitive to the student composition of schools. We simulate the efficacy of desegregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Another related explanation is that some parents may hold preferences for schools with a low concentration of ethnic minority pupils (Nielsen and Andersen, 2019), such that native parents of young children move selectively to avoid schools with high minority concentrations. Wessel and Nordvik (2019) suggested that this may be the case in Norway, and other recent studies support this notion (Bjerre- Nielsen and Gandil, 2020;Kauppinen et al, 2020;Rogne et al, 2021). Our analysis of parents and nonparents also clearly supports such an argument.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Another related explanation is that some parents may hold preferences for schools with a low concentration of ethnic minority pupils (Nielsen and Andersen, 2019), such that native parents of young children move selectively to avoid schools with high minority concentrations. Wessel and Nordvik (2019) suggested that this may be the case in Norway, and other recent studies support this notion (Bjerre- Nielsen and Gandil, 2020;Kauppinen et al, 2020;Rogne et al, 2021). Our analysis of parents and nonparents also clearly supports such an argument.…”
Section: Discussionsupporting
confidence: 85%
“…In Copenhagen, parents may apply for their child to attend a different school than their nearest school; an application that is approved if the school has extra capacity (City of Copenhagen, n.d). A recent study from Denmark (Bjerre-Nielsen and Gandil, 2020) has shown that many parents respond to the socioeconomic and ethnic composition of their local school, and the redrawing of attendance boundaries, either by relocating or by enrolling their child in a private or a different public school. Similar studies from Norway (Rogne et al, 2021) and Finland (Kauppinen et al, 2020) have also shown that schools are an important factor in parents’ moving decisions.…”
Section: Theoretical Perspectives and Research On Segregation And Nat...mentioning
confidence: 99%
“…A critical limitation of all of our results so far is that they do not factor in the likelihood of complex system dynamics that could manifest if districts actually did adopt the rezonings described here-for example, neighborhood relocation (e.g., "white flight") in response to unfavorable rezonings (Bjerre-Nielsen & Gandil, 2020;Reber, 2005) or the disproportionate use of school choice by families to opt for other district or charter options that enable them to circumvent the effects of changing boundaries. All of these could affect the extent to which the methods proposed thus far can actually help districts achieve greater racial and ethnic integration in schools.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Fraudulent or illegal activities that involve users bypassing the rule of law are ubiquitous across applications and arise as users seek to strategically obtain some benefit that would otherwise not be attainable within the bounds of lawful conduct. For instance, in transportation networks, users often drive above the speed limit to reduce their travel times, and, in school choice contexts, parents often misreport their home addresses to admit their children to better public schools [1]. Similar issues of users engaging in fraud arise in other domains, including labor markets [2], strategic classification [3,4], non-market allocation mechanisms [5], and resource allocation [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, fraudulent or illegal activities can be detrimental, as even a few users engaging in such activities can compromise safety, result in disproportionate negative externalities to particular groups of the population, or hamper efficiency. In transportation networks, users driving above the speed limit can compromise road safety, and, in school choice settings, sophisticated gaming by some parents, who typically belong to higherincome strata, often adversely affects users not engaging in such practices [1]. Moreover, in healthcare contexts, the manipulation of patient's priority by transplant providers in organ transplant waiting lists often results in significant reductions in organ donations [7,8].…”
Section: Introductionmentioning
confidence: 99%